Hemostasis at Extremes of Body Weight - Hunt, Beverley J. (Seminars in Thrombosis and Hemostasis, 2018)
Extremes of body weight are not uncommon in the modern world and include anorexia nervosa (AN) and obesity. Both conditions are associated with increased morbidity and mortality: AN has the highest mortality rate of all mental illnesses and unfortunately obesity has reached epidemic proportions and is a well-recognized risk factor for cardiovascular disease including venous thromboembolism (VTE). This article summarizes the current understanding of hemostatic changes of these extremes of body weight. The hemostatic changes of AN have not been well described. Severe AN is associated with pancytopenia with decreased bone marrow cellularity, which causes a mild thrombocytopenia. Platelet hyperaggregability has been recognized in AN and has been attributed at least in part to increased adrenoceptor density. Obesity and the metabolic syndrome are associated with prothrombotic changes, which have been well characterized and related to complex adipocyte-induced inflammatory changes, including increased levels of plasminogen activator inhibitor type 1, von Willebrand factor, fibrinogen, and other evidence of increased coagulation and platelet activation. Accumulating evidence suggests a significant role for increased tissue factor expression and signaling in this relationship, with increased tissue factor expression present in adipose and possibly systemic tissues, induced by adipose-generated cytokines. Intriguingly, the hemostatic changes do not seem to increase with increasing BMI, although the risk of VTE increases with BMI, suggesting that decreased venous flow due to venous enlargement may play the most important role in increased VTE risk with obesity.
Keywords: obesity; anorexia nervosa; body mass index; hemostasis